Lock-in thermography : basics and use for evaluating electronic devices and materials /: basics and use for evaluating electronic devices and materials. ([2018]) - Breitenstein, O (Otwin); Warta, W (Wilhelm); Langenkamp, M (Martin), 1964-
No abstract available